Emotion regulation as a mediator on the relationship between emotional awareness and depression in elementary school students - Wang, Ruian; Li, Haoyue; Sang, Biao; Zhao, Yuyang (Frontiers in Psychology, 2023)
As a cognitive skill, emotional awareness plays a fundamental role in emotional intelligence and significant effect on the development of individuals’ social adaptation. However, the role of emotional awareness in children’s social adaptation, especially emotional development, remains unclear, the current study sought to determine the significant influence of emotional awareness in children’s emotional development. By using cross-sectional and longitudinal study designs, the current study explored the relationship between emotional awareness and children’s depression, as well as the mediation effect of emotion regulation on this relationship. The sample comprised 166 Chinese elementary school students (89 girls and 77 boys) ranging from 8 to 12 years old. After adjusting for demographic variables (gender, grade, etc.), the results showed that children with high emotional awareness were less likely to adopt expressive suppression as an emotion regulation strategy and had lower depression levels currently and in the future. In contrast, children with low emotional awareness were more likely to use suppression strategies and showed higher depression levels. Thus, the results indicated that emotional awareness could predict children’s current and future depression status. Meanwhile, emotional regulation strategies are an important mediating variable explaining the relationship between emotional awareness and children’s depression. Implications and limitations were also discussed.